PENENTUAN KADAR HASIL PRODUK AlF3 BERDASARKAN PERBEDAAN SUHU DENGAN METODA TITRASI ZIRCONIUM CHLORIDA - Risma Sari; Inggardipta Usman (Politeknik ATI Padang, 2019)
Non-fertilizer products are functions as added ingredients or manufacturing products in other industries. AlF3 is a non-fertilizer product that functions as an ingredient in the aluminum smelting process. Aluminum fluoride (AlF3) is an inorganic compound used mainly in the aluminum process. AlF3 has a character that is difficult to dissolve in water and slightly soluble in acidic solutions. Determination of AlF3 levels is done by reacting 1 mole of AlF3 with 3 moles of NaF which is known to be excessive. Determination of AlF3 levels is carried out according to company standards namely IK - 39 - 4210 with a limit of acceptance of AlF3 levels of 94%. Sodium Fluoride (NaF) compound which is a colorless solid compound that dissolves easily in water. NaF functions as an AlF3 mixture material that forms the Na3AlF6 reaction. The method used for analysis of AlF3 levels is the Zirconium Chloride (ZrCl4) titration method. ZrCl4 titration is a method of acid-base titration in which the secondary standard solution is acidic and the primary is basic. The ZrCl4 method is very suitable because of its high solubility and acidic nature which can react and bind excess NaF compounds in the Na3AlF6 reaction. The results of determining AlF3 levels at 500 oC were 94.08%, at 550 oC for 30 minutes heating, 95.35%, and at 550 oC heating for 60 minutes at AlF3 94.79%. The results of this test temperature optimization is carried out, a more optimal temperature and a better percentage of AlF3 levels, namely at a temperature of 550 oC and at a heating time of 60 minutes, because at that temperature and time the release of crystal water and free water is more optimal and does not damage AlF3.